A PROTOTYPE MONITORING ELECTRICITY SYSTEM 220V OF WIND POWER PLANT (PLTB) BASED ON THE INTERNET OF THINGS: INTERNET OF THINGS - Hermanto, Yuli (Internet of Things and Artificial Intelligence Journal, 2021)
Abstract - Electrical energy is a human daily need that cannot be separated, even the need for electrical energy has increased every year. This is evident from the construction of renewable energy plants in areas with potential. In this thesis, a control and monitoring system for a vertical turbine wind power plant prototype will be made using the internet based on IoT (Internet of Things) technology. Where the IoT technology here, the author uses the Thingspeak and Blynk applications which are used to monitor the electrical energy output from the wind power plant (PLTB) and the output from the 220V inverter. The purpose of using IOT technology is to make it easier to monitor and control the voltage, current and output power of wind power plants from anywhere and anytime via the internet. For the manufacture of this tool in need of a voltage sensor, current sensor, relay, LCD and NodeMCU. The voltage sensor uses PZEM 004T which functions to read the value of voltage, current, cos phi and frequency, relay1 serves to limit the output voltage from the dynamo generator and relay2 to limit the output voltage to 220V in case of equipment problems, NodeMCU functions to process data read from the sensor, this NodeMCU already equipped with a WIFI module that functions to send data to an internet server so that it can be controlled and monitored anywhere and anytime. The results of the tests carried out measurements for 2 hours on the load of the iron, fan, television, 1 phase AC motor, soldering iron, dispenser, laptop charger, incandescent lamp, and refrigerator using the 004T PZEM sensor resulted in an error of 0.28% - 0.3%.